2018
DOI: 10.1002/cncr.31397
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of future health and cancer risk in adult survivors of childhood cancer: A report from the Childhood Cancer Survivor Study

Abstract: A substantial subgroup of survivors were unconcerned about their future health and subsequent cancer risks, even after exposure to treatments associated with increased risk. These survivors may be less likely to engage in beneficial screening and risk-reduction activities. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
7
22
3
1
Order By: Relevance
“…We found that approximately 60.3% of all survivors reported not being worried about subsequent neoplasms, which was somewhat higher than the rate of 40% reported by Gibson et al 1 Many survivors in our cohort (48.6%) did not believe they were at risk of developing late effects. Survivors reported an average of 3.8 treatment-related late effects (range, 0-19 late effects; standard deviation, 3.6), most commonly fatigue (41.9%), memory/learning difficulties (33.7%), and emotional issues (33.4%).…”
Section: Perceptions Of Future Health and Cancer Risk In Adult Survivcontrasting
confidence: 75%
See 4 more Smart Citations
“…We found that approximately 60.3% of all survivors reported not being worried about subsequent neoplasms, which was somewhat higher than the rate of 40% reported by Gibson et al 1 Many survivors in our cohort (48.6%) did not believe they were at risk of developing late effects. Survivors reported an average of 3.8 treatment-related late effects (range, 0-19 late effects; standard deviation, 3.6), most commonly fatigue (41.9%), memory/learning difficulties (33.7%), and emotional issues (33.4%).…”
Section: Perceptions Of Future Health and Cancer Risk In Adult Survivcontrasting
confidence: 75%
“…Survivors reported an average of 3.8 treatment-related late effects (range, 0-19 late effects; standard deviation, 3.6), most commonly fatigue (41.9%), memory/learning difficulties (33.7%), and emotional issues (33.4%). We found that approximately 60.3% of all survivors reported not being worried about subsequent neoplasms, which was somewhat higher than the rate of 40% reported by Gibson et al 1 Many survivors in our cohort (48.6%) did not believe they were at risk of developing late effects. Survivors perceived themselves to be at risk of developing an average of 4.2 future late effects (range, 0-16 late effects; standard deviation, 3.6).…”
Section: Perceptions Of Future Health and Cancer Risk In Adult Survivcontrasting
confidence: 75%
See 3 more Smart Citations